Numerical study on flexural and bond-slip behaviours of GFRP profiled-concrete composite beams with groove shear connector. (15th January 2023) - Ge, Wenjie; Zhang, Zhiwen; Guan, Zhongwei; Ashour, Ashraf; Ge, Yue; Chen, Yiwen; Jiang, Hongbo; Sun, Chuanzhi; Yao, Shan; Yan, Weihua; Cao, Dafu
Highlights: The bi-linear traction-separation model was used to investigate the bond-slip behavior between GFRP profile and concrete. The CDP model was adopted for normal concrete and RPC, and the orthotropy of GFRP profile was taken into consideration. The effect of various parameters on flexural behavior of GFRP profiled-concrete composite beams was conducted. Abstract: GFRP profiled-concrete composite beams with groove shear connectors are analyzed using finite the element (FE) analysis. The concrete damaged plasticity (CDP) model was adopted for normal strength concrete (NSC) and reactive powder concrete (RPC). The orthotropic behaviour of GFRP profile was taken into consideration, and the bi-linear traction-separation model was used to investigate the bond-slip behavior between GFRP profile and concrete. Furthermore, parametric studies were conducted to investigate the effects of strength and the cross-sectional dimensions of concrete, strength (orthotropy), and the cross-sectional dimensions (the web height and the thickness of FRP plate). Numerical analysis results correlate well with experimental results. Based on numerical analysis, the composite beam with shear connectors spacing at 100 mm has a deflection-limit load of 21.4 % higher than the specimens with 150 mm spacing. It is possible to improve the bonding behavior of interfaces by using groove shear connectors. The ultimate load and deformation, and pseudo-ductility were significantly improved by using RPC with high strength and toughness (ultimate compressive strain). GFRP profiles with greater orthotropy coefficients provide fully utilized concrete's compressive strength, preventing premature crushing and enhancing composite structure stiffness. Flexural performance of the composite beams can be improved efficiently by choosing the appropriate sectional size during design and construction.